TINDAKAN SOSIAL TOKOH UTAMA DALAM NOVEL AKU MASENJA KARYA RUMASI PASARIBU: KAJIAN SOSIOLOGI SASTRA - Lestari, Wijayanti Dwi; Pramono, Dedi (MIMESIS, 2021)
This research is motivated by the importance of one’s actions in dealing with problem in everyday life, including the social life of the main character in the novel. This research aims to determine the forms of social behavior of the main character in the novel Aku Masenjaby Rumasi Pasaribu. Social behavior theory refers to the theory social behavior from a male expert from Germany named Maximilian Weber or often called Max Weber. The research subject used is the novel Aku Masenjaby Rumasi Pasaribu. The object this research is the social behavior of the main character based on Max Weber’s theory. This research is a qualitative descriptive study. The data analysis technique uses the reading technique and the note taking technique. Then the results of the data analysis are presented in descriptive form. The results of this study indicate that the dominant form of social behavior that often appears in Aku Masenja is affective social behavior in the form of falling in love, anger, sadness, and suprise. While other actions such as behavior of instrumental rationality in the form of making decision, the desire to make parents happy, and the desire to protect students who are affected by the problem of values rationality behavior in the form moral values and religious values, tradisional behavior in the form of Pasemah community groups, the customs of a tribe in Bengkulu, the use of regional languages only a few forms appear.